GREEN SYNTHESIS OF SILVER NANOPARTICLES USING LUFFA ACUTANGULA ROXB. VAR. AMARA. LIN. AND IT’S ANTIBACTERIAL ACTIVITY. - R. SYED MOIDEEN; A. LAKSHMI PRABHA (International Journal of Pharma and Bio Sciences, 2014)
Aqueous leaf extract of Luffa acutangula Roxb. Var. amara. Lin. was used for the synthesis of silver nanoparticles using antibacterial activity. The silver nanoparticles formation was confirmed by the color change of plant extracts (SNPs) and further confirmed with the help of UV – Vis spectroscopy and Fourier Transform Infra Red (FTIR). The absorption spectra of silver nanoparticles studied using the UV-VIS spectroscopy had absorbance peak at 420 nm. The antibacterial activities of silver nanoparticles were studied using human pathogenic bacterial strains was used in Escherichia coli, Klebsiella pneumonia, Proteus vulgaris, Pseudomonas aeruginosa, Salmonella paratyphi, and Staphylococcus aureus. The zone of inhibition was higher in Klebsiella pneumonia and zone of inhibition lower in Staphylococcus aureus. The move towards an extracellular synthesis of Ag+ nanoparticles using dried biomass appears to be cost effective, eco-friendly method of nanoparticles synthesis.